1990
DOI: 10.1007/bf00001673
|View full text |Cite
|
Sign up to set email alerts
|

Fish community structure, spatial distribution and feeding ecology in a beaver pond

Abstract: SynopsisThe fish community of a small (2.7 ha) Ontario beaver pond was analyzed relative to predictions based on its small size, shallow depth, brief existence and isolation from more permanent water bodies. The predictions were: (1) species richness will be lower than that of more permanent water bodies in the area, (2) fish will be mainly of small body size, (3) species will be randomly distributed across habitats, and (4) there will be a high degree of diet overlap between species and age classes. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Community dietary overlap values would be further reduced if bluntnose minnow, which consumed mainly detritus and had a dissimilar diet to all other species, were incorporated in the overlap estimation. Keast (1985b) and Keast & Fox (1990) also found low dietary overlap within fish communities. Keast & Welsh (1968) and Ringler & Johnson (198 1) found that rock bass feeding activity peaked from late evening to early morning, which is consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Community dietary overlap values would be further reduced if bluntnose minnow, which consumed mainly detritus and had a dissimilar diet to all other species, were incorporated in the overlap estimation. Keast (1985b) and Keast & Fox (1990) also found low dietary overlap within fish communities. Keast & Welsh (1968) and Ringler & Johnson (198 1) found that rock bass feeding activity peaked from late evening to early morning, which is consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Within the sunfish pair of species, pumpkinseeds had higher glycolytic enzyme activity than bluegill, which may be part of a strategy for hypoxia tolerance (Farwell et al, 2006). Water bodies with seasonal or diurnal hypoxia often support pumpkinseed sunfish populations, but lack bluegill sunfish (Keast and Fox, 1990).…”
Section: Scaling Of Metabolic Enzymesmentioning
confidence: 99%
“…Indeed, many such waterbodies experience periodic winterkills, resulting in the high mortality of fishes that are either poorly adapted evolutionarily to living in hypoxic waters, or which are unable to find a refuge from the hypoxic conditions (Magnuson and Karlen 1970;Magnuson et al 1985 and references therein). Fish species differ widely in their ability to tolerate hypoxia (see Moore 1942;Davis 1975;Melnychuk and Chapman 2002) and as a result, the fish communities that inhabit hypoxic waterbodies often differ from those that inhabit normoxic waterbodies in the same area (Tonn and Magnuson 1982;Rahel 1984;Keast and Fox 1990).…”
Section: Introductionmentioning
confidence: 99%